Thermodynamic Control of the Carbon Budget of a Peatland. Issue 6 (15th June 2018) - Worrall, Fred; Moody, Catherine S.; Clay, Gareth D.; Burt, Tim P.; Kettridge, Nicholas; Rose, Rob
Abstract: The transformations and transitions of organic matter into, through, and out of an ecosystem must obey the second law of thermodynamics. This study considered the transition in the solid components of the organic matter flux through an entire ecosystem. Organic matter samples were taken from each organic matter reservoir and fluvial transfer pathway in a 100% peat‐covered catchment (Moor House National Nature Reserve, North Pennines, UK) and were analyzed by elemental analysis and bomb calorimetry. The samples analyzed were as follows: bulk aboveground and belowground biomass; individual plant functional types (heather, mosses, and sedges); plant litter layer; peat soil; and samples of particulate and dissolved organic matter (POM and DOM). Samples were compared to standards of lignin, cellulose, and plant protein. It was possible to calculate: enthalpy of formation ( Δ H f OM ); entropy of formation ( Δ S f OM ); and Gibbs free energy of formation ( Δ G f OM ) for each of the samples and standards. The increase (decreasing negative values) in Δ G f OM through the ecosystem mean that for all but litter production, the transformations through the system must be balanced by production of low (large negative values) Δ G f OM products, not only CO2 or CH4 but also DOM. The change in Δ G f OM down the peat profile shows that reaction of the soil organic matter decreases or even ceases at depth and the majority of the reaction has occurred above 40 cm below the surface. This approach represents a new objective way to test and trace organic matter transformations in and through an ecosystem. Key Points: Thermodynamic consideration of elemental analysis allows the prediction of the fate of carbon fixed as primary production Change in the Gibbs free energy of formation of the naturally occurring organic matter ( Δ G f OM ) shows that changes in the peat profile must be balanced by production of CO2, CH4, or DOM Organic matter accumulates in peatlands because further reaction becomes thermodynamically inhibited with depth in the peat profile